Impact of Contract Farming on Income : Linking Small Farmers, Packers, and Supermarkets in China - Miyata, Sachiko; Minot, Nicholas; Hu, Dinghuan (2012)
This study compares contract and non-contract growers of apples and green onions in Shandong Province, China in order to explore the constraints on participation and the impact of contract farming on income. We find little evidence that firms prefer to work with larger farms, though all farms in the area are quite small. Using a Heckman selection-correction model, we find that contract farming raises income even after controlling for observable and unobservable household characteristics. These results suggest that contract farming can help raise small-farm income, though questions remain regarding the number of farmers that can be brought into such schemes.